The effects of hawker influence and local gastronomy involvement on authenticity, personal nostalgia, and hawker cultural identity - Chua, Bee-Lia; Kim, Seongseop (Sam); Badu-Baiden, Frank; Yong, Rachel Yuen May; Kim, Bona; Gedecho, Ermias Kifle; Han, Heesup (Emerald Publishing, 2024)
Purpose: This study elucidated the connections among the influence of Singaporean hawkers, local gastronomy involvement, and the three dimensions of authenticity (objective, constructive, and existential). Furthermore, it investigates how personal nostalgia affects the cultural identity of hawkers. Design/methodology/approach: A self-administered questionnaire was created to assess hawker influence, gastronomy involvement, authenticity, personal nostalgia, and hawker cultural identity. Survey data was gathered from 401 Singapore residents aged 18 and older. Findings: Results of the structural equation modeling revealed various significant aspects of hawker influence, including physical and social environments, uniqueness and cultural significance, and hygiene and food safety. Hawker influence and local gastronomy contributed to objective authenticity, which, in turn, affected constructive and existential authenticity, ultimately shaping personal nostalgia and hawker cultural identity. Practical implications: The study offers guidance for stakeholders in sustaining hawker culture, emphasizing authenticity’s role and the importance of nostalgia in identity formation. By aligning with the progressive nature of Singapore, these implications aim to ensure the continued thriving of this invaluable legacy for generations to come. Originality/value: The study affirms relationships between hawker influence, local gastronomy involvement, and authenticity constructs. It emphasizes the hawker’s role and gastronomy involvement in influencing individuals’ perceived authenticity and accentuates the potential for authenticity in strengthening national branding.